Autosynchronization of two unbalance motors - Dinh, Nguyen Van; Hung, Nguyen Dac (Vietnam Journal of Mechanics, 1996)
In the present paper are presented some observations about the phenomenon of autosynchronization of two unbalance motors on a platform moving in a plane.